2020
DOI: 10.1007/s00384-020-03732-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of perineal application of prophylactic negative-pressure wound therapy for prevention of wound-related complications after abdomino-perineal resection: a systematic review

Abstract: Background Closed perineal wounds often fail to heal by primary intention after abdomino-perineal resection (APR) and are often complicated by surgical site infection (SSI) and/or wound dehiscence. Recent evidence showed encouraging results of prophylactic negative-pressure wound therapy (pNPWT) for prevention of wound-related complications in surgery. Our objective was to gather and discuss the early existing literature regarding the use of pNPWT to prevent wound-related complications on perin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…27,28 A few meta-analyses have confirmed that the use of negative pressure wound therapy could reduce the risk of SSI and other wound-related complications after APR. 17,19,29 Negative pressure suction with irrigation has been reported to be an efficient technique for the management of deep SSI. 30 Therefore, negative pressure drainage with irrigation is becoming a main trend in the prevention and treatment of complicated deep SSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 A few meta-analyses have confirmed that the use of negative pressure wound therapy could reduce the risk of SSI and other wound-related complications after APR. 17,19,29 Negative pressure suction with irrigation has been reported to be an efficient technique for the management of deep SSI. 30 Therefore, negative pressure drainage with irrigation is becoming a main trend in the prevention and treatment of complicated deep SSI.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recently, the use of prophylactic negative-pressure wound therapy for prevention of wound-related complications showed encouraging results in terms of reduction of SSI after APR. 19 But this continuous negative pressure device was set on the incision surface. Therefore, it played a minor role in deep or presacral space infection.…”
Section: Introductionmentioning
confidence: 99%
“…When the wound fails to heal, a conventional negative pressure wound therapy (NPWT) device can be considered. In a recent systematic review, the use of NPWT represents an encouraging tool in reducing surgical site infection and wound dehiscence in these patients [35]. Once the perineum is sutured, pneumoperitoneum is reinduced.…”
Section: Surgical Steps Of Miles' Operationmentioning
confidence: 99%
“…Both studies found that the perineal hernia rate was significantly lower in biologic mesh reconstruction as compared to primary closure and the operation time and hospital stay were shorter after primary perineal closure [ 125 , 126 ]. Other studies have shown a lower incidence of surgical site infection using prophylactic negative-pressure wound therapy to prevent wound-related complications in surgery, with a risk reduction of about 25% to 30% [ 127 ].…”
Section: Surgical Managementmentioning
confidence: 99%